2020
DOI: 10.2147/cmar.s243495
|View full text |Cite
|
Sign up to set email alerts
|

<p>Fucoidan Induces Apoptosis and Inhibits Proliferation of Hepatocellular Carcinoma via the p38 MAPK/ERK and PI3K/Akt Signal Pathways</p>

Abstract: Purpose: Fucoidan is a natural bioactive product with broad therapeutic applications. Hepatocellular carcinoma (HCC) is a common malignancy of the liver associated with a relatively high mortality rate; thus, effective treatments are urgently needed. Here, the effects of fucoidan on HCC and the underlying mechanism were explored. Methods: The proliferation and apoptosis of two HCC cell lines (BEL-7402 and LM3) treated with different concentrations of fucoidan or saline were assessed. The levels of proliferatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 50 publications
(49 reference statements)
3
35
1
Order By: Relevance
“…Duan et al showed that fucoidan plays a significant role in inhibiting cell proliferation in BEL-7402 and LM3 cell lines through the p38MAPK/ERK pathway [ 82 ]. Fucoidan administration results in the upregulation of NDRG-1/CAP43, mediated by the inhibition of hepatocarcinoma cells.…”
Section: Anticancer Potential Of Fucoidan: Insights From Recent Studiesmentioning
confidence: 99%
“…Duan et al showed that fucoidan plays a significant role in inhibiting cell proliferation in BEL-7402 and LM3 cell lines through the p38MAPK/ERK pathway [ 82 ]. Fucoidan administration results in the upregulation of NDRG-1/CAP43, mediated by the inhibition of hepatocarcinoma cells.…”
Section: Anticancer Potential Of Fucoidan: Insights From Recent Studiesmentioning
confidence: 99%
“…It is revealed that FPS may reduce UA damage to HK-2 cells via the JNK signaling pathway. Many studies have shown that FPS plays an anti-cancer role through the MAPK pathway [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In HCC late stages, autophagy promotes survival, metastasis, and EMT via activation of the TGFβ pathway, P53 degradation, and chemotherapy resistance of HCC [ 167 ]. Inhibitors of main signaling pathways such as PI3K/Akt, MAPK/ERK, and JAK/Stat3 can induce autophagy and cell death in HCC [ 168 , 169 ]. Small molecules like rapamycin, Mitoxantrone (PI3K/mTOR inhibitors), and Erlotinib/Cetuximab (EGFR inhibitors) are thought to activate cellular autophagy and apoptosis in various HCC cell lines [ 167 , 170 ].…”
Section: Introductionmentioning
confidence: 99%